Diagnosis and treatment of obstructive sleep apnea - Salamah, Fahad Saleh Bin; Alfayez, Hiba Mohammed Al; Melibary, Raghad Taha (International Journal Of Community Medicine And Public Health, 2022)
Obstructive sleep apnea (OSA) has become a health issue of high prevalence. The prevalence is rising between 1990-2010 by approximately 30%, with absolute increases of 4.2% in women and 7.5% in men. This condition is characterized by a breathing disorder of partial or complete upper airway obstruction leading to increased resistance to airflow and potential cessation of breathing during sleep. Its multifactorial etiology Such etiologies involve obesity, craniofacial anatomy, and the use of stimulants and medications to reduce muscle tension. This review aims to summarize the recent diagnosis and treatment modalities of OSA. The database PubMed and google scholar were searched for relevant published records. A total of 39 articles were collected randomly limited to the English language. We placed no restrictions on the date of publication. Evidence from methodological studies indicate that undiagnosed OSA is associated with hypertension, cardiovascular disease, stroke, and daytime sleepiness. Thorough clinical and instrumental examinations should precede a proper diagnosis selection. The primary goal of treatment is reducing the Patient’s symptoms, depending on the severity of the patient’s condition. OSA can be treated in different ways, including behavioral therapy, medical device, surgery, and pharmacological therapies. There are limitations in dental school about education and training of OSA and oral appliances (OA). OSA teamwork must include both qualified sleep physicians and dentists. The Orthodontist plays a critical role in evaluating and treating OSA patients, choosing the right oral appliance, and assessing and adjusting the appliance.